Evaluation of the papermaking potential of Ailanthus altissima - Ferreira, Paulo J. (2013)
In this work, Ailanthus altissima (tree-of-heaven) wood was analyzed for its chemical, morphological and papermaking properties. The A. altissima wood was cooked under kraft conditions using different active alkali charges and then handsheets were produced with the pulps having a kappa number of 16. Based on structural, strength and optical data it was found that the kraft pulp of A. altissima is not suitable to be used alone for the production of printing and writing papers. Notwithstanding, the handsheets exhibit a favorable value of brightness in comparison to those produced from Eucalyptus globulus pulp (with similar kappa number). Therefore, the wood of A. altissima seems to have a good potential to be used as a partial substitute of the main raw material of the Portuguese pulp industry. In fact, the results showed that when beaten E. globulus and A. altissima pulps were mixed (50:50 w/w), the papermaking properties were comparable to those of beaten eucalypt kraft pulps. Therefore, the use of A. altissima wood seems promising for the production of uncoated wood-free papers, which has advantages both from an economical and environmental perspective.